Music and nonverbal communication in long-stay institutions for aged: new resources for the training of musicians to humanizing hospitals - Eliseth Ribeiro Leão; Victor Flusser (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This is a qualitative study that aimed to examine the nonverbal communication mediated by music among musicians (Centre de Formation de Musicien Intervenant) and institutionalized aged, and produce a new education strategy for the course of musicians training developed at the University Marc Bloch, in France. After consent and approval by ethical review board data were collected from scenes filmed (without editing), for a previous documentary of Music in Hospitals Project. Two musical encounters were analyzed for decoding nonverbal communication and scenes of six similar musical encounters were included in the educational video to illustrate the theoretical content to be taught. The decoding of non-verbal communication was carried out by units of analysis (taken from the video camera). In the first musical encounter were assessed 68 units of analysis and in the second were assessed 50 units of analysis. The interpersonal relations were characterized by facial expressions, types of smile and ways of looking. The affective touch occurred several times between musicians and aged persons. The close distance between the participants was observed. The data analysis resulted in the production of an educational video with audio in Portuguese and in French.